Acculturation preferences and behavioural tendencies between majority and minority groups: The mediating role of emotions. (2nd March 2016) - López‐Rodríguez, Lucía; Cuadrado, Isabel; Navas, Marisol
Abstract: The main goal of this research was twofold. First, we aimed at determining how acculturation preferences and emotions were related to specific intergroup behavioural tendencies towards majority and minority groups. Second, we aimed at developing an intergroup behavioural tendencies scale that differentiates between valence (facilitation and harm) and intensity (active and passive). The role of intergroup contact was also examined, as it is a known predictor of intergroup prejudice. In order to fulfil these goals, we carried out two studies. InStudy 1, Spanish participants ( N  = 279) answered a questionnaire about Moroccans (a devalued group) or Ecuadorians (a valued group) by reporting their acculturation preferences for immigrants, their positive and negative emotions, quantity of contact with them and behavioural tendencies towards them. InStudy 2, Moroccans ( N  = 92) and Ecuadorians ( N  = 87) assessed Spaniards on these measures. Results confirmed the structure of the new behavioural tendencies scale across four groups of participants. Overall, findings also showed that acculturation preferences and quantity of contact indirectly predicted behavioural tendencies through positive emotions. This research contributes to knowledge on how the majority and minority's acculturation preferences are related to their emotions and specific dimensions of intergroup behavioural tendencies, confirming the predominant mediating role of positive emotions in this process.